Modal Analysis of Cantilever Beam with Various Crack Surfaces - Danavicknesvaran M Sekhar,; Mohamad, Zaleha (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This research employs ANSYS software to conduct modal analysis on a cantilever beam, exploring the effects of different crack surfaces and materials on vibration responses. The objectives include vibration analysis for various crack locations and surfaces, Finite Element (FE) analysis, and discussion of vibration responses and identification of crack levels. The experimental analysis through ANSYS simulation, provides a cost-effective and time-efficient alternative to physical testing. Findings indicate consistent natural frequency patterns across materials and crack surfaces, with mild steel exhibiting higher values and aluminium showing lower frequencies. Mild steel consistently demonstrates stable and predictable deformations, positioning it as a robust choice for fixed-end beams. The study recommends mild steel for its superior performance in natural frequencies, resilience to cracks, and deformation control, underscoring the importance of material selection in ensuring structural integrity under varying degrees of crack severity.